SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN PADA PT. SULTRA INTI RODA PERKASA MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) DAN SIMPLE ADDITIVE WEIGHTING (SAW) - Wayan Sriwidani; Ika Purwanti Ningrum; Rahmat Ramadhan (Informatics Engineering Department of Halu Oleo University, 2016)
Abstract PT. Sultra Inti Roda Perkasa company engaged in the restaurant where the recruitment process still involves subjective consideration that lead to decisions that are not appropriate. Based on these problems we need a system to support the implementation of the decision-making process more objective and provide appropriate recommendations. Realizing this decision support system, using the method of Weighted Product (WP) and Simple Additive Weighting (SAW) as comparison method. WP is a method of decision-making by way of multiplication to connect rating attributes, where each attribute rating should be raised to a first weight attribute is concerned whereas, SAW is a method that is also known as the weighted summation method. The basic concept SAW method is to find the sum of the weighted performance rating for each alternative on all attributes.The results of this analysis, a decision support applications recruitment, where the implementation of this application shows that WP and SAW in the process appraisal at reception prospective employee has a value the same result, if both methods have a weight value the same one. Keywords— Decsision Support System, Recommendation System, Weighted Product, Simple Additive Weighting, Employees Recruitment